2020
DOI: 10.22270/ajprd.v8i1.653
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Micropropagation Culture Method

Abstract: Micropropagation is a vegetative propagation conducted under controlled and aseptic conditions in the microenvironment of the culture vessel, which have the all growth requirements of a plant in the natural conditions. Recently different techniques of propagation have been developed which could facilitate large scale production of plants and for the improvement of the species. An overview on the in vitro propagation via meristem culture, callus culture and protoplast culture etc. are presented here. Today micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Since food insecurity is still a serious global challenge, it is imperative todevelop a direct shoot organogenesis protocol for crops of economic importance as these protocols enable us to produce large numbers of new high-quality plantlets in a relatively short time and space. Micropropagation is a low-cost technology, and plantlet derived from micropropagation helps in plants germplasm conservation (Gupta et al, 2020). In this study, micropropagation method was developed for two common varieties of taro in Kenya, that is, Dasheen and Purple Wild.…”
Section: Discussionmentioning
confidence: 99%
“…Since food insecurity is still a serious global challenge, it is imperative todevelop a direct shoot organogenesis protocol for crops of economic importance as these protocols enable us to produce large numbers of new high-quality plantlets in a relatively short time and space. Micropropagation is a low-cost technology, and plantlet derived from micropropagation helps in plants germplasm conservation (Gupta et al, 2020). In this study, micropropagation method was developed for two common varieties of taro in Kenya, that is, Dasheen and Purple Wild.…”
Section: Discussionmentioning
confidence: 99%
“…Micropropagation can be carried out using nodal explants, shoot tips, or leaf segments, which are immersed within a specific growth media. BAP (6‐benzylaminopurine) and NAA (naphthaleneacetic acid) are commonly used as regulators to promote shoot proliferation, thus increasing the enzyme production rate [44] …”
Section: Production Of Plant Proteasesmentioning
confidence: 99%
“…BAP (6benzylaminopurine) and NAA (naphthaleneacetic acid) are commonly used as regulators to promote shoot proliferation, thus increasing the enzyme production rate. [44] The costs associated to regulators compounds are crucial to scale up of micropropagation techniques to produce highquality roots. An optimized growth medium is required for each particular enzyme according to the explant types in order to achieve a feasible yield.…”
Section: Micropropagation and Somatic Embryogenesismentioning
confidence: 99%
“…Plant micropropagation is one of the best alternatives for crop improvement and shows a special significance in multiplication through a vegetative approach. This minimizes the risk of pathogen accumulation and the slow proliferation rate in generative multiplication, which in turn, causes a loss in both crop quantity and quality [39][40][41][42]. Several studies have shown the positive impacts of AgNP augmentation for callus induction, shoot generation, and growth (Table 1).…”
Section: Silver-nanoparticles In Crop Improvementmentioning
confidence: 99%